Feasibility study of incorporation of glass into porous asphalt made of RCA - Lim, Su-Qi. (2013)
The feasibility study of incorporating waste glass and Recycled Concrete Aggregates (RCA) into Porous Asphaltic (PA) mix was investigated in this project. The project was conducted in the context for light-duty applications like pedestrian and cycling paths. Incorporation of glass with RCA followed closely due to plausible results obtained from incorporation of only RCA in PA mix done by past researches.